ODaCCI: Ontology-guided Data Curation for Multisite Clinical Research Data Integration in the NINDS Center for SUDEP Research - Cui, Licong (AMIA Annu Symp Proc, 2017)
Sudden Unexpected Death in Epilepsy (SUDEP) is the leading mode of epilepsy-related death. The Center for SUDEP Research (CSR) is an NINDS-funded Center Without Wall’s initiative aimed at prospectively creating a comprehensive clinical research resource for SUDEP. This resource consists of a growing set of data and biological samples of a statistically significant cohort of patients at an elevated risk, best represented by the Epilepsy Monitoring Unit (EMU) patient population. The Informatics and Data Analytics Core (IDAC) of CSR has developed a state-of-the- art informatics infrastructure, to integrate patient data captured in multiple EMU’s at a greatly accelerated pace. Data quality assurance is a priority of IDAC. This paper reports our approach, Ontology-guided Data Curation for Multisite Clinical Research Data Integration (ODaCCI), to address the challenging task of centralized data curation while new data is continuously generated and integrated from distributed sites. ODaCCI leverages the Epilepsy and Seizure Ontology not only for upstream data capture, but also for supporting a range of quality assurance tasks such as data quality monitoring, data update, and data reports. Between October 2014 and February 2016, ODaCCI has integrated phenotypic and electroencephalogram signal data of 629 patients from 7 clinical sites, while supporting continuous and asynchronous data quality enhancement overtime.